The Association Between Religion and Healthcare Professionals' Attitudes Towards the Conscience Clause. A Preliminary Study From Poland - Justyna Czekajewska; Dariusz Walkowiak; Jan Domaradzki (Frontiers Media S.A., 2023)
Objectives: This study was designed to determine the relationship between religion and healthcare practitioners' attitudes towards conscience clauses in Poland.Methods: We developed a survey assessing impact of religion on attitudes healthcare professionals towards the conscience clause. These questions were explored using a sample of 300 Polish healthcare professionals.Results: The results indicate that religiosity was a significant predictor of acceptance of conscience clauses. It also influenced healthcare practitioners' opinions on medical professionals that should be granted the right to conscience clauses and medical services that may be denied on moral grounds. There was also a significant relationship between healthcare practitioners' religiosity and their eagerness to use conscience clauses in a situation of moral conflict. Finally, religious healthcare practitioners were more concerned about the personal consequences of using this right in a medical environment.Conclusion: This study shows that at the same time, both religious and non-religious healthcare professionals believed that the Polish regulations regarding conscience clause are unclear and inaccurate, therefore leading to misinterpretation and abuse regulation of law.